Dual interfacial modifications of an organic solar cell by self-assembled monolayers - Hsu, Po-Jen; Tedla, Abebe; Zharnikov, Michael; Tai, Yian (Journal of photochemistry and photobiology, 2022)
Whereas modification of individual interfaces in organic photovoltaic (OPV) devices by self-assembled monolayers (SAMs) is a well-established procedure, simultaneous engineering of several interfaces therein represents still a challenge, with an open outcome. In this context, in the present study, we test a dual modification approach by the example of a model OPV device, featuring in particular indium tin oxide (ITO) cathode, ZnO cathode buffer layer (CBL), and a polymer heterojunction active layer (AL). The dual modification involved both ITO/ZnO and ZnO/AL interfaces, which were engineered with several SAMs bearing electron-withdrawing and electron-donating tail groups. Characterization of these interfaces and the CBL suggests that the major effects of the SAM-engineering were optimization of the interfacial electrical contacts and interfacial dipole as well as improved morphology of the CBL and lower density of defects therein. Interestingly, at the single interface modification, a larger positive effect was achieved with the -OCH3 terminated SAM than with the -CF3 decorated one. In contrast, at the dual modification, an inverse effect was observed, with a better performance of the -CF3 termination, pointing to a complex synergetic mechanism. Significantly, the dual modification resulted in a noticeably larger improvement of the photovoltaic characteristics of the OPV devices as compared to the standard approach, manifesting the advantages of the dual strategy.